The affective dimension of far right rhetoric in the classroom: the promise of agonistic emotions and affects in countering extremism. Issue 2 (4th March 2021) - Zembylas, Michalinos
ABSTRACT: This essay draws on the concept of agonistic emotions and affects to think with some of the arguments of Chantal Mouffe's political theory and discusses what this means pedagogically in handling far right rhetoric in the classroom. To show the possibilities of this theorization of agonistic emotions and affects, the essay puts in conversation Mouffe's work on agonistic pluralism with post-Deleuzian affect theory. I make an argument that post-Deleuzian affect theory enables the theorization of agonistic emotions and affects as an intersection of language, desire, power, bodies, and politics that can be engaged with and channeled democratically in classroom debates. The essay leans on Mouffe's work and post-Deleuzian affect theory to make a political and pedagogical intervention into the terrain of countering extremism in education. This intervention offers a theoretical and pedagogical way of addressing the tensions emerging from the affective dimension of far right rhetoric in classroom spaces.